Majelis Arbain Memanfaatkan Moment Maulid untuk Membentengi Aqidah Masyarakat di Kecamatan Gunung Tabur Kabupaten Berau - Abd. Qodir Jailani; Ahmad Muthohar; Dani Dani; A. Alvian Fitriyanto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The entry of the Wahabi group has an impact on various religious activities, especially the Amaliah of Ahlussunnah Wal Jamaah, some conditions in the affected community are their unwillingness to carry out tahlilan, maulidan, talqin and this also has an impact on the decline in public trust in religious figures who continue to uphold the aqidah of Ahlussunnah Wal Jamaah. Gunung Tabur District, Berau Regency is an area with a significant impact of the Wahabi group. Their lack of knowledge about the evidence or basics of the Amaliah of Ahlussunnah Wal Jamaah resulted in the Gunung Tabur sub-district community, which initially mostly carried out the Amaliah, decreasing drastically, one of which was the reading of the maulid, due to limited human resources to preach to fortify the community from this, reducing interest in carrying out the Amaliah above. The Arbain Assembly utilizes the moment of the month of Maulid as a moment for training and mentoring carried out by going to the community from house to house or from village to village by studying the books of scholars who explain the basics of the Amaliah of Ahlussunnah Wal Jamaah.